Revitalizing Verbal Communication: Exploring the Linguistic Landscape of International BIPA Students - Zahra, Arsy; Tiawati, Refa Lina; Rahmat, Wahyudi (Journal of Humanity Studies, 2023)
This research is motivated by the presence of international students from various countries with diverse cultures and varying language abilities compared to Indonesia. International students are those who come from outside Indonesia, meaning that Indonesian is not their first language. International BIPA students aim to master the four language skills, one of which is speaking. Therefore, international students need to have the ability to speak effectively and correctly in verbal or oral communication. The research aims to analyze the forms of grammar and vocabulary usage in the verbal communication of international BIPA students at Andalas University. This research is qualitative in nature with a descriptive methodology. The research respondents are international students currently engaged in learning activities at Andalas University. Data collection is conducted through observation, interviews, recording techniques, and note-taking. Data analysis is carried out using the interactive data analysis method developed by Miles and Huberman. Based on the data analysis and discussion, it is found that international BIPA students can understand and use grammar and vocabulary effectively in oral communication. They can comprehend and use grammar and vocabulary in spoken language, such as personal pronoun usage, noun phrase structure, negation words, simple sentence construction, question word usage, demonstrative pronoun usage, the verb "ada" (there is/there are), preposition usage, affix verbs, adverb usage, conjunction usage, expressions and greetings, and vocabulary related to general topics. However, international students face difficulties in terms of grammar, particularly regarding the accurate pronunciation and sound pronunciation when communicating verbally. These challenges arise from cultural and language differences with their home countries. In this research, two forms of grammar usage were not found in spoken communication: the use of gradable adjectives and the use of position and location. Keywords: International BIPA students, Verbal communication skills, Grammar and vocabulary usage and Language challenges and cultural differences